« It’s Never Just One Road » : Genga-Idowu et la prostitution dans l’espace urbain de Nairobi - Muriungi, Colomba (Études littéraires africaines)

(untitled) (Association pour l'Étude des Littératures africaines (APELA), 2011)
My article is a reading of Genga-Idowu’s Lady in Chains with an intention to show how she attempts to rewrite the presentation of the prostitute figure in a Kenyan urban space by figuring prostitution as an institution that is useful in questioning and revising economic power relations between men and women. Genga-Idowu shows that women can reliably accumulate income from prostitution and emancipate themselves from the economic disadvantages of postcolonial Kenya. I examine specific traits of the prostitute figure and the spaces within the city that this writer utilizes to revise and disavow Kenyan male writers and socio-cultural conception of the prostitute. Thus prostitution will be projected as a business and a potential alternative road that makes women economically powerful and frees them from other kinds of disadvantages that characterize their lives.